If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 64m * m Multiply m * m 4 = 64m2 Solving 4 = 64m2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-64m2' to each side of the equation. 4 + -64m2 = 64m2 + -64m2 Combine like terms: 64m2 + -64m2 = 0 4 + -64m2 = 0 Add '-4' to each side of the equation. 4 + -4 + -64m2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -64m2 = 0 + -4 -64m2 = 0 + -4 Combine like terms: 0 + -4 = -4 -64m2 = -4 Divide each side by '-64'. m2 = 0.0625 Simplifying m2 = 0.0625 Take the square root of each side: m = {-0.25, 0.25}
| 4x^2y-10xy^3= | | 450-3x=100 | | -15-2x=-6+3x+11 | | 6*x-3=21 | | -26+(-17)= | | -26+-17= | | 8*12+4=88 | | 0=16x+4 | | 4=64m*2 | | 6(x-5)+6=3(x-7) | | 6(x-1)-3(1-x)=9x-7 | | V=1/3a^2h | | y=0.2x+0.8 | | t*t=8-2n | | -7/8+x=-7/12 | | y=0.2+0.8 | | 4+4x=10x+10 | | -14=x-5 | | 18x^2+47x-56=0 | | 21(2-x)+21x=44 | | 1.4(2x-1)+1.4=.7(4x-10)+7 | | 4(3+5g)+6g= | | ((3x-1)/2)-((x+1)/2)=3 | | 5-7x=-6x+12 | | 4(x-2)=6x | | -5(3-q)=5q-15 | | -7k+3.1k+2.7k-2= | | 31/2*11/2 | | ((3x-1)/2)+((x+1)/2)=3 | | 7+(8-2)=n+5 | | 6+7=8x-13 | | (-7m^3*n*7p^9)(-8m^4*n^5*p^4)= |